Customsteel trading e-customer servicing and expert system - Masunungure, James D. (Midlands State University, 2017)
The aim of research study is to construct a web based system that enables customers to order products and services online. This study aims to make products and services availability a must to all customers in need of the service. The project was guided by objectives listed below:  To develop a system that facilitate real time processing capabilities by enabling customers to register online and receive their login details on their mobile phones.  To develop a system that have a robust database handling ability that keeps track of which customers buy which products and then send them promotional alerts through email or sms.  To create a system that provides built in tracking and reporting metrics.  To allow customers to view products, services and prices online.  To equip customers with a Multiple Payment Mode Compatible system then upload proof of payment though the system  The system must enable the users to prioritize the requests. Different problems require different priorities.  To create a system with an online helpdesk with a single point of contact to end users. Data was collected from system users using information gathering techniques which include interviews, questionnaires, and observations. The collected data was then converted into meaningful information (during the analysis phase) with the use of tables and diagrams as well as explanations to shed more light on the pictorial presentations. The system design used the client server architecture to implement the inference mechanism while the database component was implemented using MySQL. The user interface was implemented using HTML and PHP. Testing and validation techniques were applied to make sure the system meets its intended purpose and also satisfy user requirements.